Quantitative comparison of wideband low-latency phase-locked loop circuit designs for high-speed frequency modulation atomic force microscopy - Miyata, Kazuki; Fukuma, Takeshi (Beilstein Journal of Nanotechnology, 2018)
A phase-locked loop (PLL) circuit is the central component of frequency modulation atomic force microscopy (FM-AFM). However, its response speed is often insufficient, and limits the FM-AFM imaging speed. To overcome this issue, we propose a PLL design that enables high-speed FM-AFM. We discuss the main problems with the conventional PLL design and their possible solutions. In the conventional design, a low-pass filter with relatively high latency is used in the phase feedback loop, leading to a slow response of the PLL. In the proposed design, a phase detector with a low-latency high-pass filter is located outside the phase feedback loop, while a subtraction-based phase comparator with negligible latency is located inside the loop. This design minimizes the latency within the phase feedback loop and significantly improves the PLL response speed. In addition, we implemented PLLs with the conventional and proposed designs in the same field programmable gate array chip and quantitatively compared their performances. The results demonstrate that the performance of the proposed PLL is superior to that of the conventional PLL: 165 kHz bandwidth and 3.2 μs latency in water. Using this setup, we performed FM-AFM imaging of calcite dissolution in water at 0.5 s/frame with true atomic resolution. The high-speed and high-resolution imaging capabilities of the proposed design will enable a wide range of studies to be conducted on various atomic-scale dynamic phenomena at solid–liquid interfaces.
Keywords: calcite dissolution process; frequency modulation atomic force microscopy; high-speed atomic-resolution imaging; phase-locked loop